EFFECTIVITY OF DOLOMITE ADSORBENT IN PURIFICATION OF Mn AND Cu FROM ACID MINE DRAINAGE - Akhyar; Hesti Meilina; Fauzi Djuned; Sri Mulyati; Abrar Muslim (RADJA PUBLIKA, 2023)
The mining industry raises many environmental problems in the ecosystem, one of which is the emergence of acid mine drainage. Because of this issue, this study was conducted to see the performance of dolomite adsorbents in purifying acid mine drainage at iron ore mining in Aceh Besar, Indonesia. The adsorption of Cu2+ metal ions using dolomite adsorbents has the best equilibrium result at a contact time of 15 minutes, the efficiency at equilibrium reaches 92.97%, and the absorption capacity reaches 9.07 mg/g at an initial measured concentration of 19.5 mg/L with an adsorbent weight of 0.2 gr. On the other hand, Mn2+ has the best equilibrium in 30 minutes with an efficiency of 95.17% and an adsorption capacity of 0.92 mg/g at a measured concentration of 5.8 mg/L and an adsorbent weight of 0.6 gr. The obtained kinetic model is a pseudo second order.